2014
DOI: 10.1007/s10661-014-3625-9
|View full text |Cite
|
Sign up to set email alerts
|

Urban stream syndrome in a small, lightly developed watershed: a statistical analysis of water chemistry parameters, land use patterns, and natural sources

Abstract: The relationships among land use patterns, geology, soil, and major solute concentrations in stream water for eight tributaries of the Kayaderosseras Creek watershed in Saratoga County, NY, were investigated using Pearson correlation coefficients and multivariate regression analysis. Sub-watersheds corresponding to each sampling site were delineated, and land use patterns were determined for each of the eight sub-watersheds using GIS. Four land use categories (urban development, agriculture, forests, and wetla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 59 publications
2
27
0
2
Order By: Relevance
“…This suggests that, for this area, the impact of large state‐maintained highways is not necessarily different from that of smaller, locally managed roads, although the opposite was found in the Adirondacks of New York (Kelting et al, 2012). Overall, our results corroborate other studies that indicate a connection between urbanization and its resultant increase in impervious surface area and increased road salt concentration in fresh water bodies (Cunningham et al, 2009; Medalie 2012; Cassanelli and Robbins, 2013; Eyles et al, 2013; Dailey et al, 2014; Halstead et al, 2014; Corsi et al, 2015). …”
Section: Discussionsupporting
confidence: 91%
“…This suggests that, for this area, the impact of large state‐maintained highways is not necessarily different from that of smaller, locally managed roads, although the opposite was found in the Adirondacks of New York (Kelting et al, 2012). Overall, our results corroborate other studies that indicate a connection between urbanization and its resultant increase in impervious surface area and increased road salt concentration in fresh water bodies (Cunningham et al, 2009; Medalie 2012; Cassanelli and Robbins, 2013; Eyles et al, 2013; Dailey et al, 2014; Halstead et al, 2014; Corsi et al, 2015). …”
Section: Discussionsupporting
confidence: 91%
“…Toor 2016). as well as studies on the concentrations of ion macronutrients in water (Halstead 2014). The case determines the value of classification criterion as above may also be a matter of judgment.…”
Section: Resultsmentioning
confidence: 99%
“…We witnessed direct sewage discharge from houses and solid waste dumping in river banks mainly in the downstream settlement areas. Halstead et al [29] concluded that anthropogenic sources of pollution such as synthetic fertilizers and discharge from septic systems and sewers significantly contributed to 'urban stream syndrome' Common effects of urbanization on stream ecosystems have been referred to as the "urban stream syndrome" (Walsh et al [30]), and there is a strong association between water quality and increased settlement area.…”
Section: Discussionmentioning
confidence: 99%